The Strategy of The Leadership Protocol and Communication Section in Improving Employee Performance at The Regional Secretariat of Manado City - Doddy,; Kandou, Selpius R.; Mandagi, Marthinus (Technium Social Sciences Journal, 2024)
This research aims to analyze the strategy of the Leadership Protocol and Communication Section (Prokopim) at the Manado City Regional Secretariat in improving employee performance. The research method used is a qualitative method. The focus of the research is strategies for improving employee performance using SWOT (Strength, Weakness, Opportunities, Threats) analysis. The research results show that the strategy of the Leadership Protocol and Communication Section of the Manado City Regional Secretariat in improving employee performance based on the SWOT analysis method (IFAS, EFAS, and SWOT analysis quadrants is "Aggressive (Growth Oriented Strategy)" meaning the Leadership Protocol and Communication Section of the Manado City Regional Secretariat has internal strengths and opportunities so that its strengths and opportunities can be an advantage for the Leadership Protocol and Communication Section of the Manado City Regional Secretariat in improving employee performance. 5 (five) Strategic recommendations can be implemented, namely 1) Aggressively in meeting human resource and facility needs and budget; 2) Aggressively in coordinating to increase supervision; 3) Aggressively in increasing employee motivation; 4) Aggressively in providing sanctions for efforts to improve work discipline; 5) Aggressive in carrying out human resource development.